Изотопный состав углерода и серы раннепротерозойских пород центральной части Украинского щита - Фомин, Ю.А.; Демихов, Ю.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
The new data on the isotopic composition of C graphite and S sulfides of the Khmelevsky, Lipnyazhsky, Dubinovsky, and Savransky districts in Early Proterozoic rocks of the Bugskaya series are presented. On the base of the comparison of these districts with some manifestations (including Au, U) in the stratigraphic analogs of this series in the borders of the Central Part of the Ukrainian Shield, their isotopic-geochemical identity is shown. So, the existence of the common, perspective on uranium and gold ores, lithological-stratigraphic level is confirmed.